Analysis of Management Performance using the RGEC Method Approach (Risk Profile, Good Corporate Governance, Earnings, and Capital) at PT Bank SulutGo in 2018-2023 - Salim, George Bryan; Saerang, David P. E.; Tangkuman, Steven J. (PT FORMOSA CENDEKIA GLOBAL, 2025)
Banking plays an important role in society, especially in building the economy. Bank Indonesia issued PBI No. 13/1/PBI/2011 concerning the assessment of the health level of commercial banks using the RGEC method (Risk Profile, Good Corporate Governance, Earning, Capital). This study aims to determine the management performance of Bank SulutGo by using the RGEC method. The research method used in this research is descriptive method with qualitative approach and the data used is secondary data from Bank SulutGo's published financial statements. The results showed that the management performance of NPL, LDR, and GCG ratios were in healthy and quite healthy criteria. The management performance of the ROA ratio shows excellent management performance, being on healthy criteria and the BOPO and CAR ratios are on healthy criteria.